2015
DOI: 10.1371/journal.pone.0118765
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Neuronal Glucose Transporter Expression Reveals Metabolic Choice in a HD Drosophila Model

Abstract: Huntington’s disease is a neurodegenerative disorder caused by toxic insertions of polyglutamine residues in the Huntingtin protein and characterized by progressive deterioration of cognitive and motor functions. Altered brain glucose metabolism has long been suggested and a possible link has been proposed in HD. However, the precise function of glucose transporters was not yet determined. Here, we report the effects of the specifically-neuronal human glucose transporter expression in neurons of a Drosophila m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 85 publications
(103 reference statements)
4
40
0
Order By: Relevance
“…As previously described, knockdown of ND23 in neurons causes shortened lifespan (Besson, Alegría, Garrido-Gerter, Barros, & Li evens, 2015). As previously described, knockdown of ND23 in neurons causes shortened lifespan (Besson, Alegría, Garrido-Gerter, Barros, & Li evens, 2015).…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…As previously described, knockdown of ND23 in neurons causes shortened lifespan (Besson, Alegría, Garrido-Gerter, Barros, & Li evens, 2015). As previously described, knockdown of ND23 in neurons causes shortened lifespan (Besson, Alegría, Garrido-Gerter, Barros, & Li evens, 2015).…”
mentioning
confidence: 61%
“…Indeed, we previously observed that the overexpression of the human glucose transporter hGluT3 is able to suppress the lethality induced by the ND23 RNAi (Besson et al, 2015). Indeed, we previously observed that the overexpression of the human glucose transporter hGluT3 is able to suppress the lethality induced by the ND23 RNAi (Besson et al, 2015).…”
Section: Glucose Transporter Overexpression Rescues the Alterationsmentioning
confidence: 90%
“…We show that FAs are used to restore OCR only when glucose is low in the sensitive STR (Figure 6). Indeed, overexpression of glucose-6-phosphate dehydrogenase, the major enzyme for the pentose phosphate pathway (PPP) (Legan et al, 2008), or overexpression of a glucose transporter (Besson et al, 2015) extends lifetime in flies expressing 93 glutamine repeats. The CBL in HdhQ(150/150) animals is replete with amino acid precursors for these pathways and this region is more resistant to toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of G6PD extended lifespan of transgenic HD fly significantly 99 Drosophila transgenic model Overexpression of G6PD in Drosophila neurons delayed proteostasis decline with age and extend lifespan 21 Transgenic mice with moderate expression of G6PD Moderate transgenic overexpression of G6PD in mice extended healthspan and median lifespan of females 24 Development of a G6PD agonist G6PD agonist AG1 effectively activated G6PD and reduced oxidative stress in G6PD-deficient human fibroblasts and zebrafish embryo 22 Abbreviations: G6PD, glucose-6-phosphate dehydrogenase; OGD, oxygen-glucose deprivation; PPP, pentose phosphate pathway. TANG | 14291…”
Section: Models Key Findings Referencesmentioning
confidence: 99%
“…A more direct indication of a beneficial effect of G6PD in HD is demonstrated by a Drosophila transgenic model. For flies carrying the exon 1 of the human huntingtin gene with 93 glutamine repeats (HQ93), overexpression of G6PD was shown to significantly increased lifespan and reduced eye neurodegeneration …”
Section: G6pd and Neurodegenerative Diseasesmentioning
confidence: 99%